Land Demand and Security Requirement in the Balance of Iraqi-Kuwaiti Relations: (A Geopolitical Assessment Study) - Mohammed, Saad Jassim (Al-Adab Journal, 2020)
The problems of the borders between Iraq and Kuwait emerged in after the Iraq invaded Kuwait which caused the issuance of international decisions resulting from the influence of the United States of America that led an international war to force Iraq to withdraw from Kuwait. Those decisions were under Chapter Seven and forced Iraq to implement them compulsively. One of these international decisions was to redraw the borders between the two countries, and such decision granted Kuwait many concessions at the expense of the Iraqi lands bordering Kuwait. These lands are rich with oil (Southern Rumaila fields). Such decision was primarily political and security in nature. It did not taken into consideration, in the same way, the historical and legal aspects, and most importantly the geographical one when implementing the decision. The decision was based on granting the land to achieve or reach the security of Kuwait, but in this way, it has established several foundations and problems that may arise in the future. From this standpoint, we, as geographers and observers of the political and security conditions between the two countries, should have a role in providing realistic and rational solutions that satisfy all parties, leading to the preservation of regional and international peace and security, especially as the two countries are located in the most distinguished and dangerous and risky areas of international competition, in the world of (Arab Gulf). In conclusion, we are aware that the land achieves security and security may not be achieved by stealing the lands of the other party.